STRATEGI PENINGKATAN PENDAPATAN ASLI DAERAH DARI RETRIBUSI PASAR DI KABUPATEN SUKOHARJO - Reydonnyzar Moenek; Eko Budi Santoso (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2019)
Retribution is one of the sources of Local original income (LOI). This paper is the result of research describing strategies for increasing LOI from market service retribution (market retribution) and exploring various possible strategies that might still be possible to increase market retribution collection in Sukoharjo Regency. The research design used is descriptive and explorative qualitative research. Data collection techniques used were interviews, observation, and documentation. The analysis technique uses SWOT analysis and discrepancy analysis techniques. The results showed that the strategies which had been implemented so far had not shown success in achieving the target of collecting market retribution which had a large contribution to the Local Original Income (LOI). There are still six strategies that can be implemented by the Local Government of Sukoharjo Regency to increase the results of the collection of market retribution that will increase its LOI. It is recommended to take six steps according to the strategiesy that has not been done or that has not been done much so far.